RESTORASI EKOSISTEM PADANG LAMUN MELALUI TEKNOLOGI BIO-FADs TREE DENGAN BAHAN DASAR RUMPUT LAUT PADA PERIKANAN DEMERSAL - Kantun, Wayan; Wulandari, Sri; Angreni, Husni; Susaniati, Warda; Kabangnga, Arnold; Hasbi, Ibnu Malkan; Idrus, Muhammad Ikhsan (LPPM Institut Pendidikan Nusantara Global, 2024)
Coastal water ecosystems in general have experienced damage as a result of fishing that is not environmentally friendly. This unfriendly fishing causes the fish's feeding grounds to be damaged so that fishing activities in coastal areas need to involve fishing aids to collect fish. The fishing aids implemented are in accordance with the fishing objectives to be achieved. The implementation of fishing aids aims to attract attention and bring fish to the area where the attractor is installed, making it easier to catch. One of the fishing aids used is Biological Fish Aggregating Devices (Bio-FADs Tree) or live FADs equipped with Kappaphycus alvarezii seaweed which acts as an attractor to attract fish so they can be easily caught. This service is carried out in Mamuju waters for the purpose of catching demersal fish. The service is carried out using trap fishing equipment. The results of the service showed that the catches obtained were Pink ear emperor (Lethrinus lentjan), Redbelly yellowtail fusilier (Caesio cuning), Streaked spinefoot (Siganus javus), batik Vermiculated spinefoot (Siganus vermiculatus) and Orange-spotted spinefoot (Siganus gutattus), White-spotted spinefoot (Siganus canaliculatus), and Surf parrotfish (Scarus rivulatus). All of the catches are fish of important economic value